Imperfect prey selectivity of predators promotes biodiversity and irregularity in food webs. (22nd September 2015) - Ryabov, Alexey B.; Morozov, Andrew; Blasius, Bernd; Fussmann, Gregor
Abstract Ecological communities are often characterised by many species occupying the same trophic level and competing over a small number of vital resources. The mechanisms maintaining high biodiversity in such systems are still poorly understood. Here, we revisit the role of prey selectivity by generalist predators in promoting biodiversity. We consider a generic tri‐trophic food web, consisting of a single limiting resource, a large number of primary producers and a generalist predator. We suggest a framework to describe the predator functional response, combining food selectivity for distinctly different functional prey groups with proportion‐based consumption of similar prey species. Our simulations reveal that intermediate levels of prey selectivity can explain a high species richness, functional biodiversity, and variability among prey species. In contrast, perfect food selectivity or purely proportion‐based food consumption leads to a collapse of prey functional biodiversity. Our results are in agreement with empirical phytoplankton rank‐abundance curves in lakes.